Exponentially tunable voltage controlled quadrature oscillator - Sotner, Roman; Jerabek, Jan; Petrzela, Jiri; Domansky, Ondrej; Jaikla, Winai; Dostal, Tomas (My University, 2017)
This paper deals with appropriate method of tunability extension in quadrature oscillators. Exponential dependence of frequency of oscillations on DC control voltage is created in lossless integrators by utilization of two exponentially controlled variable gain amplifiers and diamond transistors. Proposed solution maintains all beneficial features (especially independent levels of output waveforms on tuning process) of the oscillator concept employing two lossless integrators in the single loop and electronically controllable negative resistor serving for adjusting of condition of oscillations. PSpice verifications based on simulations of macromodels of used active devices confirmed doubled tunability range in comparison to standard linear control of frequency obtained for the same change of DC driving voltage.
Keywords: Current conveyor; Electronic control; Exponential control; Lossless integrator; Quadrature oscillator; Tunability extension; Variable gain amplifier